2004
DOI: 10.1007/s00586-004-0738-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic electrophysiological examination in patients with lumbar spinal stenosis: Is it useful in clinical practice?

Abstract: From among a large battery of electrophysiological tests, only the minimal latency of the tibial F-wave and the latency of the soleus H-reflex exhibit changes after walk loading in patients with LSS. These are minimal but statistically significant. Dynamic electrophysiological examination can illustrate the pathophysiology of NC in LSS, but from a practical point of view its contribution to the differential diagnostics of LSS or diabetic polyneuropathy is limited by an absence of established cut-off values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
5
16
0
3
Order By: Relevance
“…They measured the soleus H-reflex, tibial F-wave, and motor evoked potentials to the abductor hallucis muscle, both before and after the ETT. Only the minimal latency of the tibial F-wave and the latency of the soleus H-reflex exhibited changes after walk loading in patients with LSS (32). In a similar study by Adamova et al (33), increased chronodispersion of the tibial F-wave distinguished LSS patients from polyneuropathy patients and healthy controls.…”
Section: Im Ma Ag Gi In Ng Gmentioning
confidence: 70%
See 1 more Smart Citation
“…They measured the soleus H-reflex, tibial F-wave, and motor evoked potentials to the abductor hallucis muscle, both before and after the ETT. Only the minimal latency of the tibial F-wave and the latency of the soleus H-reflex exhibited changes after walk loading in patients with LSS (32). In a similar study by Adamova et al (33), increased chronodispersion of the tibial F-wave distinguished LSS patients from polyneuropathy patients and healthy controls.…”
Section: Im Ma Ag Gi In Ng Gmentioning
confidence: 70%
“…These changes consisted of unelicitability or increased latencies, which reversed over the course of 15 minutes following ambulation (31). Adamova et al (32) used an exercise treadmill test (ETT) as a dynamic variable in patients with LSS diagnosed by CT, diabetic polyneuropathy patients, and a group of healthy control patients. They measured the soleus H-reflex, tibial F-wave, and motor evoked potentials to the abductor hallucis muscle, both before and after the ETT.…”
Section: Im Ma Ag Gi In Ng Gmentioning
confidence: 99%
“…Several authors have investigated the sensitivity of MEP in LSS or lumbosacral cord lesions and reported that the rate of abnormal MEP was increased after exercise [3,6,9,15,16]. Baramki et al [6] reported that MEPLT was significantly prolonged after walking a certain distance and concluded that exercise significantly increased the sensitivity of MEP in detecting roots under functional compression in LSS.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic electrophysiological examination in patients with lumbar spinal stenosis This paper by Adamova [1] reports a negative result, dynamic studies are not of value, although they demonstrate changes, such changes can be present in patients without claudication. Spinal stenosis, especially in the mild diabetic patient is a difficult diagnosis, and it is a shame that these examinations do not help.…”
Section: Spinal Stenosismentioning
confidence: 99%